Investigating the Reggio Emilia Study Tour Experience From Conversation to Insights - Will Parnell (Networks: An Online Journal for Teacher Research, 2012)
Taking early childhood Master’s students on a Reggio Emilia Study Tour leads to making meaning of anticipatory and after-experience reflective narrative-episodes. These narrative episodes are constructed around the phenomena of anticipating the trip as well as reflecting on the experiences during and after the study tour. The experiences are then analyzed collaboratively among researchers and participants through informal discussions. Themes in each narrative episode are explored through the written narratives and then conclusions are drawn. Anticipatory themes include eagerness to see, desire to witness the image of the child in the everyday, and a concern about adopting the Reggio approach in the U.S.; and, wanting to understand documentation processes and feeling a sense of time and space in the environments. After-experience reflections bring about themes such as change as a constant reminder of humanness and barriers in language and translation; and, questioning practices at home and constructing understanding/articulating differences as reconciliation. In the conclusion, questions linger about stretching ourselves, going on the journey as learners, and finding the in-between moments. We also find new frameworks of mind where believing and seeing in new ways lead us to not “do Reggio” and instead develop our own living organism and dynamic programs as the joy in a lifetime of work approach. In the end, finding the extraordinary in the everyday emerges as an implication for future research.